Problem-based learning - A viable addition for secondary school science - West, Steve A.
This article defines and presents a rationale for problem-based learning in science teaching. The process of problem-based learning is outlined and its benefits explored. The use of problem-based learning in the classroom is illustrated to support it as a viable teaching strategy for secondary school science
Keywords: Problem-based learning